Effect of Depression, Anxiety and Stress on Mental Health of Teachers - Marooj; Sajid Mahmood Alvi; Nighat Altaf; Bibi Asma Khatoon (Journal of Management Practices, Humanities and Social Sciences, 2022)
This study was conducted to examine the relationship between Depression, Stress and Anxiety with Mental Health among Teachers. Depression, Stress, Anxiety Scale (21 item) was used to collect the information from the participants developed by Lovibond and Lovibond (1995), Secondly, Mental Health Index Scale was used to study mental health of teacher developed by Veit and Ware (1983). Sample was comprised of 200 participants from different schools, colleges (government, private) and University of Haripur. Data was collected through convenience sampling technique with door to door survey and hypotheses were analyzed by using t test, descriptive statics, and Pearson correlation. Hypothesis of this study were supported. According to the current study, mental health and its sub-dimensions such as life satisfaction, psychological wellbeing was negatively correlated with depression, anxiety and stress. Likewise mental health and its sub dimensions such as loss of behavior and psychological distress were positively related with stress. Female instructors were more likely than male teachers to feel depression anxiety and stress which turnout to have negative impact on their mental health. The current study aimed to see if teachers' greater rates of depression, anxiety, and stress are linked to reports of mental health. The current study's findings may help psychologists and administrators better understand the requirements of the teacher population by identifying the levels and impacts of depression, anxiety, and stress on teachers. Possible interventions and policy changes may, in turn, reduce teacher burnout and increase teacher mental health status as well as improvements of students’ performance.